The Proteasome Inhibitor, MG132, Attenuates Diabetic Nephropathy by Inhibiting SnoN Degradation In Vivo and In Vitro. (9th June 2014) - Huang, Wei; Yang, Chen; Nan, Qinling; Gao, Chenlin; Feng, Hong; Gou, Fang; Chen, Guo; Zhang, Zhihong; Yan, Pijun; Peng, Juan; Xu, Yong
Abstract : Transforming growth factor- β (TGF- β ) has been shown to be involved in diabetic nephropathy (DN). The SnoN protein can regulate TGF- β signaling through interaction with Smad proteins. Recent studies have shown that SnoN is mainly degraded by the ubiquitin-proteasome pathway. However, the role of SnoN in the regulation of TGF- β /Smad signaling in DN is still unclear. In this study, diabetic rats were randomly divided into a diabetic control group (DC group) and a proteasome inhibitor (MG132) diabetes therapy group (DT group). Kidney damage parameters and the expression of SnoN, Smurf2, and TGF- β were observed. Simultaneously, we cultured rat glomerular mesangial cells (GMCs) stimulated with high glucose, and SnoN and Arkadia expression were measured. Results demonstrated that 24-hour urine protein, ACR, BUN, and the expression of Smurf2 and TGF- β were significantly increased (P < 0.05 ), whereas SnoN was significantly decreased in the DC group (P < 0.05 ). However, these changes diminished after treatment with MG132. SnoN expression in GMCs decreased significantly (P < 0.05 ), but Arkadia expression gradually increased due to high glucose stimulation (P < 0.05 ), which could be almost completely reversed by MG132 (P < 0.05 ). The present results support the hypothesis that MG132 may alleviate kidney damage by inhibiting SnoN degradation and TGF- β activation, suggesting that the ubiquitin-proteasome pathway may become a new therapeutic target for DN.